MATERNAL SIMULATOR - GONZALEZ QUINONES PAULINA; LOERUP LISE; GARVIK TOR INGE; IANKE JENS PETTER (2012)
Device for simulating birth and birth related complications, the device being adapted to be attached to a real human being 5 and having an outer skin 1 with a simulated vaginal opening 6, said opening being adapted to be situated adjacent the lower part of the person 5, further having a simulated uterus 18 adapted to contain a foetus manikin 29, said uterus 18 having an opening 20 coinciding with the vaginal opening 6 of the outer skin 1, said uterus 18 further a uterus simulator 51 for simulating uterus conditions between a simulated atonic state and a simulated contracted state, and further comprising a first conveyor 27 for conveying simulated blood from a blood container 33 to the simulated vaginal opening 6, when the simulated uterus 53 is in the atonic state.